2006
DOI: 10.1002/hlca.200690210
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements in Model Peptide‐Type Radicals via Intramolecular Hydrogen‐Atom Transfer

Abstract: In fond memory of our friend and colleague, Professor Hanns Fischer, and in recognition of his distinguished contributions to chemistry Intramolecular H-atom transfer in model peptide-type radicals was investigated with high-level quantum-chemistry calculations. Examination of 1,2-, 1,3-, 1,5-, and 1,6[C $ N]-H shifts, 1,4-and 1,7[C $ C]-H shifts, and 1,4[N $ N]-H shifts (Scheme 1), was carried out with a number of theoretical methods. In the first place, the performance of UB3-LYP (with the 6-31G(d), 6-31G(2d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 38 publications
5
31
0
Order By: Relevance
“…This is consistent with the high radical mobility indicated by theoretical and experimental observations [26,46]. As shown in Scheme 2, after the radical moves to the side-chain ␤-carbon via hydrogen abstraction, it facilitates the cleavage of backbone C ␣ -C(O) bonds, forming an even-electron a-type ion after loss of an odd-electron carbonyl radical.…”
Section: Collisional Dissociation Of Radical Ionssupporting
confidence: 87%
“…This is consistent with the high radical mobility indicated by theoretical and experimental observations [26,46]. As shown in Scheme 2, after the radical moves to the side-chain ␤-carbon via hydrogen abstraction, it facilitates the cleavage of backbone C ␣ -C(O) bonds, forming an even-electron a-type ion after loss of an odd-electron carbonyl radical.…”
Section: Collisional Dissociation Of Radical Ionssupporting
confidence: 87%
“…The Gly-Gly dipeptide radical has been recently studied as a benchmark for hydrogen transfer reactions in peptides. 38 In the current study, the ⌬E, ⌬G 298 , and forward and reverse ⌬G ‡ are reported. Moran et al found the ⌬E and barriers at the G3͑MP2͒-RAD level of theory to be −5.5, 18.4, and 23.9 kcal/ mol, respectively.…”
Section: Quantum Mechanical Peptide Radical Rearrangementmentioning
confidence: 99%
“…It is usually initiated by hydrogen abstraction or proton transfer from the initial radical site generated in the ion formation step [35,36]. Reaction barriers for H atom transfer in several small model radicals have been reported by Moran et al [37]. They demonstrated that in the absence of side chains 1,4 [C↔C] hydrogen transfer along the peptide backbone is associated with substantial barriers of ca.…”
mentioning
confidence: 99%